Peningkatan Hasil Belajar Tema 9 Melalui Model Discovery Learning Pada Siswa Sekolah Dasar - Astuti, Dewi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2024)
The aim of this research is to improve student learning outcomes through the theme 8 discovery learning model for fourth grade students at SD Negeri Dukuhan Kerten Surakarta. This research is classroom action research (PTK). This research was carried out at SDN Dukuhan Kerten Surakarta with a total of 273 students. Data collection techniques in this research are observation, tests, and documentation. The data analysis technique used is interactive analysis, namely data reduction, data presentation, and conclusion. The results of the research show that the discovery learning model can improve learning outcomes for theme 9